Commissioning of the TileCal ATLAS hadronic calorimeter with cosmic rays and the LHC single beam - Ribeiro, Nuno Miguel Pinto Figueiredo Raimundo (2009)
Tese de mestrado, Física (Física Nuclear e Partículas), Universidade de Lisboa, Faculdade de Ciências, 2009